ANALISIS HUBUNGAN IMPOR BERAS DAN FAKTOR MUSIMAN TERHADAP HARGA GABAH DAN BERAS - Adhi P Wibowo (Pusat Kajian Anggaran, 2019)
This article aims to look at how the relationship of imported rice and harvest season against the national grain and rice prices. The method used is quantitative method with secondary data. Based on the analysis and discussion is the relationship of the price of imported rice GKP, MPD, and rice is negative and significant relationship of seasonal factors on the price of GKP, MPD, and rice is negative and significant.